Penelitian Pelayanan Perpustakaan Era Kenormalan Baru Pada Data Base Google Scholar: Narrative Literature Review - Sofia Permatasari; Rully Khairul Anwar; Siti Chaerani Djen Amar; Evi Nursanti Rukmana (Media Pustakawan, 2023)
The Covid-19 outbreak in Indonesia has changed library services into a new era of normality. This research aims to find out, (1) types of library information sources, (2) library services and (3) the role of librarians in the new normal era. This research uses the narrative literature review method so that it is expected to obtain a theoretical basis that can support in solving the problem being studied.  The number of scientific articles analyzed was 12 pieces from the Google Scholar database for the period 2020 – 2022. Researchers use the Google Scholar database because it has advantages including the availability of various scientific articles that are easily accessible, efficient in the use of cost and time.  The results and discussion show that library services in the new normal era are based on the internet and information technology. The library collection consists of repackaging information in digital format, developing open library collections and e-journals. Library services consist of librarian delivery services, social media-based library services, online reference services and digital libraries.  It is concluded that the role of library libararians in the new normal era is very important and education and training are needed in order to have competence in the field of internet and information technology which plays a very important role in library services in the new normal era.